PENGARUH QUALITY MANAGEMENT TERHADAP DAYA SAING KONTRAKTOR PADA PROYEK KONSTRUKSI GEDUNG DI KOTA BANDA ACEH - Nya' Munanta; Muttaqin Hasan; Hafnidar A. Rani (JURNAL TEKNIK SIPIL, 2016)
Abstract: This study aims to identify the dominant factors to implement quality management, and analyze the relationship and influence between the factors of the application of quality management for the competitiveness of the building contractors on construction projects in the city of Banda Aceh. The project is observed that the building construction project has been completed in the city of Banda Aceh from 2005-2015. Based on data from Construction Services Development Board (LPJK) 2016 Aceh province, the population number obtained by 102 contractors. Through equation Slovin the study sample was obtained by 51 contractors. The dominant factor in the application of quality management kosntruksi building project in the city of Banda Aceh is a factor of decision making and problem solving, with a mean value of 4.355. The relationship between the factors to implement quality management for the competitiveness contractor on the project of construction of buildings in Banda Aceh is training factors, factors focus on the customer, factors benchmarking, factor of continuous improvement, and the factor of participation and empowerment of employees have a relationship that is very high partially with Pearson correlation coefficient values 0,900. Influence factors of quality management for the competitiveness of the building contractors on construction projects in the city of Banda Aceh, the most influential factor is the participation and empowerment of employees, with a regression coefficient of 1.170. This suggests that if an enhanced employee engagement and empowerment, while the other factors constant, the competitiveness of the building contractor on construction projects in the city of Banda Aceh will increase. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi faktor dominan penerapan quality management, dan menganalisis hubungan serta pengaruh antara faktor-faktor penerapan quality management terhadap daya saing kontraktor pada proyek konstruksi gedung di Kota Banda Aceh. Proyek yang diamati adalah proyek konstruksi gedung yang telah selesai dilaksanakan di Kota Banda Aceh mulai dari tahun 2005-2015. Berdasarkan data dari Lembaga Pengembangan Jasa Konstruksi (LPJK) Provinsi Aceh Tahun 2016, jumlah populasi diperoleh sebanyak 102 kontraktor. Melalui persamaan Slovin maka sampel penelitian diperoleh sebanyak 51 kontraktor. Faktor dominan penerapan quality management pada proyek konstruksi gedung di Kota Banda Aceh adalah faktor pengambilan keputusan dan pemecahan masalah, dengan nilai mean sebesar 4,355. Hubungan antara faktor-faktor penerapan quality management terhadap daya saing kontraktor pada proyek konstruksi gedung di Kota Banda Aceh adalah faktor pelatihan, faktor fokus pada pelanggan, faktor benchmarking, faktor perbaikan berkesinambungan, dan faktor pelibatan dan pemberdayaan karyawan mempunyai hubungan yang sangat tinggi secara parsial dengan nilai koefisien korelasi Pearson 0,900. Pengaruh faktor-faktor quality management terhadap daya saing kontraktor pada proyek konstruksi gedung di Kota Banda Aceh, yang paling berpengaruh adalah faktor pelibatan dan pemberdayaan karyawan, dengan nilai koefisien regresi sebesar 1,170. Hal ini menunjukkan bahwa apabila faktor pelibatan dan pemberdayaan karyawan ditingkatkan, sedangkan faktor-faktor lainnya tetap, maka daya saing kontraktor pada proyek konstruksi gedung di Kota Banda Aceh akan semakin meningkat.